2022
DOI: 10.3389/fgene.2022.859595
|View full text |Cite
|
Sign up to set email alerts
|

Functional Variants Associated With CMPK2 and in ASB16 Influence Bovine Digital Dermatitis

Abstract: Bovine digital dermatitis (BDD) is an infectious disease of the hoof in cattle with multifactorial etiology and a polygenic influence on susceptibility. With our study, we identified genomic regions with the impact on occurrence and development of BDD. We used 5,040 genotyped animals with phenotype information based on the M-stage system for genome-wide association. Significant associations for single-nucleotide polymorphisms were found near genes CMPK2 (chromosome 11) and ASB16 (chromosome 19) both being impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…The authors noticed IL8 expression significantly increased in the M2-M3 stages of the illness, and immunohistochemistry labeling identified keratinocytes as the source, demonstrating a critical role for keratinocytederived IL8 in the pathogenesis of DD. In the same vein, functional variants linked to the CMPK2 and ASB16 genes have been shown to affect bovine digital dermatitis [41]. Additionally, Watts et al [42] noted that beta-defensin is an important indicator of active DD.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noticed IL8 expression significantly increased in the M2-M3 stages of the illness, and immunohistochemistry labeling identified keratinocytes as the source, demonstrating a critical role for keratinocytederived IL8 in the pathogenesis of DD. In the same vein, functional variants linked to the CMPK2 and ASB16 genes have been shown to affect bovine digital dermatitis [41]. Additionally, Watts et al [42] noted that beta-defensin is an important indicator of active DD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies identified the potential for genetic selection to decrease the susceptibility for digital dermatitis in cattle (Biemans et al, 2019b;Oelschlaegel et al, 2022). It would be interesting to investigate how these genotypes relate to the phenotypes based on recurrence of M2 lesions (type I, type II, and type III) as identified by Gomez et al (2015).…”
Section: Decreasing the Susceptibility Of The Hostmentioning
confidence: 99%